Single Nucleotide Polymorphism Effects on Lamb Fecal Egg Count Estimated Breeding Values in Progeny-Tested Katahdin Sires - Notter, David R.; Heidaritabar, Marzieh; Burke, Joan M.; Shirali, Masoud; Murdoch, Brenda M.; Morgan, James L. M.; Morota, Gota; Sonstegard, Tad S.; Becker, Gabrielle M.; Spangler, Gordon L.; MacNeil, Michael D.; Miller, James E. (Frontiers in Genetics, 2022)
Estimated breeding values (EBV) for fecal egg counts (FEC) at 42 to 90 days of age (WFEC) and 91 to 150 days of age (PFEC) for 84 progeny-tested Katahdin sires were used to identify associations of deregressed EBV with single-nucleotide polymorphisms (SNP) using 388,000 SNP with minor-allele frequencies ≥ 0.10 on an Illumina high-density ovine array. Associations between markers and FEC EBV were initially quantified by single-SNP linear regression. Effects of linkage disequilibrium (LD) were minimized by assigning SNP to 2,535 consecutive 1-Mb bins and using the effects of the most significant SNP in each bin for the analysis. Bonferroni correction was used to define bin-based (BB) genome- and chromosome-wide significance. Six bins on chromosome 5 achieved BB genome-wide significance for PFEC EBV, and three of those SNP achieved chromosome-wide significance after Bonferroni correction based on the 14,530 total SNP on chromosome 5. These bins were nested within 12 consecutive bins between 59 and 71 Mb on chromosome 5 that reached BB chromosome-wide significance. The largest SNP effects in this region were at 63, 67, and 70 Mb, with LD among these SNP of r2 ≤ 0.2. Regional heritability mapping (RHM) was then used to evaluate the ability of different genomic regions to account for additive variance in FEC EBV. Chromosome-level RHM indicated that one 500-SNP window between 65.9 and 69.9 Mb accounted for significant variation in PFEC EBV, and five additional 500-SNP windows between 59.3 and 71.6 Mb reached suggestive (P < 0.10) significance for PFEC EBV. Previous studies rarely identified markers for parasite resistance on chromosome 5. However, the IL12B gene at 68.5 Mb codes for the p40 subunit of both interleukins 12 and 23. Other immunoregulatory genes are also located in this region of chromosome 5, providing opportunity for additive or associative effects.